Makers vs. takers: perceived challenges to food production among agriculturalists in the United States. Issue 4 (8th August 2022) - Kohn, Craig; Anderson, Charles W.
ABSTRACT: Purpose: Numerous factors currently challenge food production in the United States, and these are likely to intensify. We sought to understand what challenges US agriculturalists find to be most salient as well as the responses they recommend. Methodology: We gained insights primarily through the analysis of transcripts from the qualitative interviews of 51 agricultural professionals throughout the United States. Findings: The participants most identified challenges that reduced their personal, economic, and environmental agency, including misinformed consumers, depressed commodity prices, increased agribusiness consolidation, ecological degradation. While they doubted the capacity for traditional forms of education and extension to address these challenges, they advocated for more opportunities for social learning and grassroots organization. Theoretical implications: These findings support prior research that seeks improved agency for people in rural communities, including social learning opportunities can lead to wider engagement of stakeholders in a manner that can lead to more effective adaptive management strategies. Practical implications and value: This work can inform how to design education and extension outreach by expanding dialogue opportunities between farmers and other agriculturalists to enhance adaptive management strategies in agriculture.